2020
DOI: 10.1016/j.ajog.2020.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Care of critically ill pregnant patients with coronavirus disease 2019: a case series

Abstract: Strengths of this study included the timely nature of our findings as the COVID-19 pandemic ensues, death tolls reach record highs, and communities adopt methods of social distancing to flatten the disease curve. Our findings are applicable to the obstetrical population who, regardless of the COVID-19 pandemic, cannot safely avoid or delay contact with hospitals compared with other patient populations because pregnancy is finite. The limited number of patients in our study was a potential weakness. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 4 publications
5
76
1
1
Order By: Relevance
“…Small international case series suggest a similar course of illness in pregnant and non-pregnant women [ 9 , [13] , [14] , [15] , [16] ]. Most studies suggest that critical illness is rare in pregnant patients but slightly increased when compared to the general population [ 8 , 11 , 13 , 17 , 18 ]. One study reported that approximately 90% of pregnant women diagnosed with COVID-19 disease recovered without needing to deliver [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small international case series suggest a similar course of illness in pregnant and non-pregnant women [ 9 , [13] , [14] , [15] , [16] ]. Most studies suggest that critical illness is rare in pregnant patients but slightly increased when compared to the general population [ 8 , 11 , 13 , 17 , 18 ]. One study reported that approximately 90% of pregnant women diagnosed with COVID-19 disease recovered without needing to deliver [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PRIORITY study, which included 179 infants born to COVID-positive mothers and 84 infants born to COVID-negative mothers, found no increased risk of preterm birth, NICU admission, and respiratory disease in the COVID-positive cohort, although NICU admission and preterm birth were increased in the sub-group of mothers testing positive 0–14 days before delivery [ 2 , 4 , [8] , [9] , [10] , [11] , [13] , [14] , [15] , 18 , [24] , [25] , [26] ]. The largest cohort study to date followed the courses of 242 COVID-19 positive pregnant women and their 248 infants through the third trimester of pregnancy and one month postpartum [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from viral respiratory illnesses such as influenza, SARS-CoV-1, and MERS suggest that pregnancy may worsen both maternal and fetal outcomes (1,2). Existing data in critically ill pregnant women with COVID-19 are mainly limited to case series or systematic reviews lacking non-pregnant controls (3)(4)(5). To better understand this potentially at-risk population, we describe the clinical course of 32 critically ill pregnant women admitted to ICUs across the United States.…”
Section: To the Editormentioning
confidence: 99%
“…As a uniquely vulnerable group, pregnant women may be predisposed to a higher risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and more complicated clinical events than the general population. There have been case reports of pregnant women with severe Letter to the Editors ajog.org COVID-19 requiring mechanical ventilation and extracorporeal membrane oxygenation (ECMO) 2,3 and reports of maternal and intrauterine fetal death. 1,4 Accumulating evidence suggests that a cytokine storm syndrome (CSS), an overactive immune response triggered by COVID-19, rather than the virus itself, is responsible for severe symptoms and deaths in patients with COVID-19.…”
mentioning
confidence: 99%